Efektivitas Model Pembelajaran dan Koordinasi Mata Tangan Terhadap Hasil Belajar Bola Basket Peserta Didik - Tirtawati, Ni Wayan; Yoda, I Ketut; Dharmadi, Made Agus; Artanayasa, I Wayan; Parwata, I Gusti Lanang Agung (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2024)
In the PJOK learning process, teachers have an important role in designing innovative learning and considering physical aspects that are in accordance with the subject matter. This study aims to determine the difference in the effectiveness of TPS and PBL learning models on the learning outcomes of students' basketball skills as a whole and students with low hand eye coordination. This type of research is a quasi-experiment with a 2x2 treatment by level design. The study population was 5th grade students in Tembuku District. The research sample was 80 students, randomly selected by simple random sampling through the groups drawing. The data collected were hand eye coordination data and learning outcomes analyzed by inferential statistics through two-way ANOVA test and LSD test. The results showed that there were differences in learning outcomes of basketball skills between students who followed the TPS and PBL models (F=5.902;p<0.05), and there are differences in learning outcomes for students with low hand eye coordination in both models (F=28.349;p<0.05).